Progress in clinical research in surgery and IDEAL. Issue 10141 (7th July 2018) - McCulloch, Peter; Feinberg, Joshua; Philippou, Yiannis; Kolias, Angelos; Kehoe, Sean; Lancaster, Gillian; Donovan, Jenny; Petrinic, Tatjana; Agha, Riaz; Pennell, Christopher
Summary: The quality of clinical research in surgery has long attracted criticism. High-quality randomised trials have proved difficult to undertake in surgery, and many surgical treatments have therefore been adopted without adequate supporting evidence of efficacy and safety. This evidence deficit can adversely affect research funding and reimbursement decisions, lead to slow adoption of innovations, and permit widespread adoption of procedures that offer no benefit, or cause harm. Improvement in the quality of surgical evidence would therefore be valuable. The Idea, Development, Exploration, Assessment, and Long-term Follow-up (IDEAL) Framework and Recommendations specify desirable qualities for surgical studies, and outline an integrated evaluation pathway for surgery, and similar complex interventions. We used the IDEAL Recommendations to assess methodological progress in surgical research over time, assessed the uptake and influence of IDEAL, and identified the challenges to further methodological progress. Comparing studies from the periods 2000–04 and 2010–14, we noted apparent improvement in the use of standard outcome measures, adoption of Consolidated Standards of Reporting Trials (CONSORT) standards, and assessment of the quality of surgery and of learning curves, but no progress in the use of qualitative research or reporting of modifications during procedure development. Better education about research, integration of rigorous evaluation into routine practice and training, and linkage of such work to awards systems could foster further improvements in surgical evidence. IDEAL has probably contributed only slightly to the improvements described to date, but its uptake is accelerating rapidly. The need for the integrated evaluation template IDEAL offers for surgery and other complex treatments is becoming more widely accepted.